Impact of Neutrophil to Lymphocyte Ratio (NLR) Index and Its Periprocedural Change (NLRΔ) for Percutaneous Coronary Intervention in Patients With Chronic Total Occlusion. (August 2017) - Li, Chenguang; Zhang, Feng; Shen, Yi; Xu, Rende; Chen, Zhangwei; Dai, Yuxiang; Lu, Hao; Chang, Shufu; Qian, Juying; Wang, Xiangfei; Ge, Junbo
We assessed the association between neutrophil to lymphocyte ratio (NLR) and chronic coronary total occlusion (CTO), as well as clinical prognosis of percutaneous coronary intervention (PCI). Patients referred for elective coronary angiography for stable angina pectoris were enrolled, including a CTO (n = 160) and a non-CTO group (n = 160). Neutrophil to lymphocyte ratio on admission and post-PCI was measured, and NLRΔ was defined as the change between the 2 values. Subgroup analysis was performed based on the value of NLRΔ (≥0.5 vs <0.5). Clinical characteristics, angiographic data, and follow-up data were recorded. Compared with the non-CTO group, the total white blood cell count, neutrophil counts, and NLR were significantly higher in the CTO group. In the NLRΔ ≥ 0.5 subgroup, the incidence of severe dissection, slow coronary flow, in-stent restenosis (ISR), and major adverse cardiac events (MACEs) was obviously higher. In multivariate analysis, NLRΔ was independently and positively associated with higher risks of ISR and MACE. The NLR could be a potential predictor of CTO, and NLRΔ is independently associated with the adverse clinical outcomes in patients who underwent PCI.